Simulations of canopy net photosynthesis and transpiration in Quercus ilex L. under the influence of seasonal drought - Sala, A; Tenhunen, J D (Agricultural and Forest Meteorology, 1996)
A mechanistically based C 3 leaf photosynthesis model combined with an empirical stomatal model and a canopy model of light interception and microclimate was used to simulate Quercus ilex canopy net photosynthesis and transpiration at l'Avic watershed (NE Spain). The model takes into account the sun-shade leaf differentiation of photosynthetic characteristics as affected by depth within the canopy. Based on field studies, simulations were carried out for two locations within the watershed along a gradient in elevation, microclimate and forest structure. Effective predictions of diurnal and seasonal courses of stomatal conductance of sun and shade leaves for different days during the year were obtained by changing a single model variable termed gF- The value of gF determined from least squares of observed vs. simulated time courses was linearly related to pre-dawn xylem water potential over critical ranges of the response curve. Response to gF in the model may to a great extent be thought of as the integrated expression of canopy response to root system generated signals or control mechanisms. For development of predictive capability, gF is extremely useful because it allows seasonal assessments of water use and carbon dioxide uptake with differing patterns in water availability. Based on simulated responses on representative clear, overcast and variable days throughout the year, only small differences in annual totals for net photosynthesis and transpiration were found between the two sites, despite large differences in soil drying. Annual estimates of canopy water loss were in close agreement with independent estimates of evapotranspiration using the hydrological input/output method.
Keywords: canopy net photosynthesis; Empirical model (voyant); Stomatal conductance; water use

Canopy structure within a Quercus ilex forested watershed: variations due to location, phenological development, and water availability - Sala, A; Sabate, S; Gracia, Carlos; Tenhunen, J D (Trees-Structure and Function, 1994)
Spatial and temporal changes in canopy structure were studied in 1988 and 1989 in a Mediterranean Q u e r c u s ilex forest in north-eastern Spain. Due to differences in precipitation patterns the 1989 growing season was drier than the 1988 growing season. Sampling was conducted in parallel at two sites which represent endpoints along a slope gradient within a watershed (ridge top at 975 m, and valley bottom at 700 m). At both sites, similar inter-annual changes in canopy structure were observed in response to differences in water availability. Samples harvested in the upper 50 cm of the canopy during 1989 exhibited a de- crease in both average leaf size and the ratio of young to old leaf and stem biomass relative to samples obtained in 1988. At the whole canopy level, a decrease in leaf pro- duction efficiency and an increase in the stem to leaf bio- mass ratio was observed in 1989. Temporal changes in canopy leaf area index (LAI) were not statistically sig- nificant. Average LAI values of Q. ilex at the two sites were not significantly different despite differences in tree stature and density (4.6 m 2 m -2 at the ridge top, and 5.3 m 2 m -2 at the valley bottom). Vertical distribution of leaves and stems within the canopy was very similar at the two locations, with more than 60% of the total LAI in the uppermost metre of the canopy. The possible significance of such an LAI distribution on the canopy carbon budget is discussed.
Keywords: Canopy structure; leaf area index; Mediterranean sclerophylls; Quercus ilex; water deficit

ASPECTOS ECOFISIOLOGICOS RELACIONADOS CON LA PRODUCCION DE LOS ENCINARES MEDITERRANEOS - Gracia, C A; Sala, A; Sabate, S (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The productivity of Quercus ilex forests is low in relation to other tree species. Waterand nutrients are often the most important limiting factors. Nevertheless the ecophysiological traits of this specie could help to explain the observed patterns of productivity. Leaf area index of european evergreen-oak forests is rather constant with values about 5. The energetic cost of formation and maintenance of the leaves of Quercus ilex accounts for more than 50 per cent of total carbon fixed by the trees. The resproutig ability of evergreen oaks could explain the high density and low mean diameter of these populations. The high proportion of living tissues in this type of structuni increases the respiration costs of the stems and branches. As a consequence, an important fraction of carhon fixed by leaves is used to maintain the structure of the community which contribute to explain the low observed net primary production of Quercus ilex forests
Keywords: ecophysiology; L.A.I.; productivity; Quercus ilex